2012
DOI: 10.1175/jamc-d-11-051.1
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and Seasonal Cycles of Cloud Occurrences, Types, and Radiative Impact over West Africa

Abstract: This study focuses on the occurrence and type of clouds observed in West Africa, a subject that has been neither much documented nor quantified. It takes advantage of data collected above Niamey, Niger, in 2006 with the Atmospheric Radiation Measurement (ARM) Mobile Facility. A survey of cloud characteristics inferred from ground measurements is presented with a focus on their seasonal evolution and diurnal cycle. Four types of clouds are distinguished: high-level clouds, deep convective clouds, shallow convec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 63 publications
9
69
0
Order By: Relevance
“…Apart from the peak in rainfall at 1500 h (1 mm h −1 ), which may reflect the one‐year sample size, the rainfall is negligible from 0900 h until midnight. A nocturnal preference for rainfall from midnight until 0700 h is consistent with the results of Rickenbach et al () and Bouniol et al (). Many days in the wet season did not experience precipitation while there were some with extremely high rainfall rates, particularly in the afternoon hours, leading to a large standard deviation.…”
Section: Resultssupporting
confidence: 91%
“…Apart from the peak in rainfall at 1500 h (1 mm h −1 ), which may reflect the one‐year sample size, the rainfall is negligible from 0900 h until midnight. A nocturnal preference for rainfall from midnight until 0700 h is consistent with the results of Rickenbach et al () and Bouniol et al (). Many days in the wet season did not experience precipitation while there were some with extremely high rainfall rates, particularly in the afternoon hours, leading to a large standard deviation.…”
Section: Resultssupporting
confidence: 91%
“…During DJF and MAM, CERES does not show a well‐marked spatial variability of LCC between the Guinean (south) and Sahel/Sahara (north) regions. Surprisingly, CERES shows LCC over the Sahel/Sahara areas (up to about 20%) during the entire year, considering that low clouds (example shallow convective systems) rarely occur over these areas except in the core of the monsoon season (Bouniol et al ., ). A spatial gradient of low‐level convection between the Sahelian and Guinean regions is thus expected due to the proximity of the latter to the ocean, leading to an influx of moisture from oceanic breezes and thus enhancing convection over these regions.…”
Section: Cloud Cover Variability In Wamentioning
confidence: 99%
“…Most studies dealing with the influence of clouds on solar radiation in WA have therefore been limited to Niamey, in the Sahel region (e.g. Bouniol et al ., ; Bourgeois et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Nazaryan et al (2008) studied the spatial and temporal variations of global cirrus based on CALIPSO. Bouniol et al (2012) and Stein et al (2011) studied the cloud structure in West Africa. Medeiros et al (2010) found that the vertical distribution of low-level cloud height is consistent with observations from the Rain in Cumulus over the Ocean (RICO) field study.…”
Section: Introductionmentioning
confidence: 99%